Analisis Optimalisasi Keuntungan dengan Integer Linear Programming (ILP) dan Metode Branch and Bound pada UMKM RM Selera - Riswanto, Reza; Sari, Rianita Puspa; Rachmat, Muhamad Taufiq (Jurnal Serambi Engineering, 2022)
A business such as MSMEs often experiences many obstacles or problems that hinder it in achieving its business goals. One of these problems is how to get the maximum profit by optimizing the product to be produced. Basically, the main purpose of building a business is to get enough profit or profit as much as possible. Optimization problems are part of society's problems, especially those engaged in the production business. Optimization is to minimize production costs and maximize sales revenue. This study aims to determine the most optimal number of products and maximize profits in optimizing Ayam Goreng production at RM Selera SMEs using the Integer Linear Programming simplex method and continued with the Branhc and Bound method. The results get with the addition of constraints ????1 ≤ 0 obtained results X1 = 0 and X2 = 2 while with constraints 1 1 obtained results X1 = 1 and X2 = 1.5. The optimum integer solution has been obtained, namely the result of LP - 4 with X1 = 0 and X2 = 2. The maximum profit obtained for the Ayam Goreng Sambal Pecel and Ayam Goreng Sambal Rica at RM Selera SMEs is Rp.1.900.000.